2012
DOI: 10.1557/opl.2012.1564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of NiAl-Mo composites produced by specially controlled directional solidification

Abstract: Mo fiber reinforced NiAl in-situ composites with a nominal composition Ni-43.8Al-9.5Mo (at.%) were produced by specially controlled directional solidification (DS) using a laboratory-scale Bridgman furnace equipped with a liquid metal cooling (LMC) device. In these composites, single crystalline Mo fibers were precipitated out through eutectic reaction and aligned parallel to the growth direction of the ingot. Mechanical properties, i.e. the creep resistance at high temperatures (HT, between 900 °C and 1200 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…To improve the fracture toughness and strength of NiAl-based materials, many techniques have been tried and many NiAl-based alloys or composites have been designed and fabricated [16][17][18][19]. Among these NiAl-based materials, the ceramic-particle-strengthened NiAl-based composites exhibit high strength, while the fiber-or lamella-phase-strengthened alloys demonstrate better fracture toughness [20][21][22]. Hu et al [23] fabricated Ni 3 (Al,Ti)and TiC-strengthened NiAl-based composite and demonstrated that the composite had ultra-high hardness and increased fracture toughness when the temperature was below 800 • C. The cleavage in the binder NiAl compound and de-cohesion of TiC from the Ni 3 (Al,Ti) interface were determined as the dominating fracture mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the fracture toughness and strength of NiAl-based materials, many techniques have been tried and many NiAl-based alloys or composites have been designed and fabricated [16][17][18][19]. Among these NiAl-based materials, the ceramic-particle-strengthened NiAl-based composites exhibit high strength, while the fiber-or lamella-phase-strengthened alloys demonstrate better fracture toughness [20][21][22]. Hu et al [23] fabricated Ni 3 (Al,Ti)and TiC-strengthened NiAl-based composite and demonstrated that the composite had ultra-high hardness and increased fracture toughness when the temperature was below 800 • C. The cleavage in the binder NiAl compound and de-cohesion of TiC from the Ni 3 (Al,Ti) interface were determined as the dominating fracture mechanism.…”
Section: Introductionmentioning
confidence: 99%